An orchestration algorithm of 5G network slicing - Heng ZHOU; Zhixian CHANG; Wujun YANG; Juan GUO (Dianxin kexue)
The network slicing is an important technology for 5G to implement the on-demand networking based on SDN/NFV network architecture.According to the main scene of 5G,a network segmentation algorithm based on GA-PSO was proposed in SDN/NFV architecture.The merit of quick converging to the global optimal solution was used to design the evaluation function of the network slicing.Using the ability of the fast random search of genetic algorithm,the updating and optimization of the network slices could be realized by using the particle swarm to chase the local optimal solution and the global optimal solution.The simulation results show that the algorithm can realize the personalized creation of multi-service scene network slices,and give full play to the advantages of SDN centralized control mode.It can reduce the energy consumption of the network and improve the utilization rate of cyber source at the same time.